Behavioral Models for Controlling Blood Pressure in Patients with Hypertension - Fernandez, Gratsia Victoria; Sudiana, I Ketut; Widyawati, Ika Yuni (Genius Journal, 2024)
Objective: This study aimed to develop a behavior model in controlling blood pressure of patients with hypertension by integrating the theory of Health Belief Model and adaption model theory by Roy. Method: This was a cross-sectional study conducted in January 2020. The population in this study was hypertension patients at the Community Health Center. The sampling technique used in this study was consecutive sampling. The instrument used in this study was a questionnaire. The data were analyzed by Partial Least Squares. Result: Modification factor, cues to action, individual beliefs and cognator significantly affected the behavior for blood pressure control with t-statistic value >1.96. Modification factors affected individual beliefs (t=10,648). Conclusion: This behavioral model can assist nursing in developing strategies to improve blood pressure control behavior in hypertensive patients. The behavior of the hypertensive patients was possibly improved by the involvement of the health worker by routinely educating the patients and their family related to hypertension and how to control blood pressure and also related to stress and how to manage it as well as with support from the family in self-care management and lifestyle modification.